2023
DOI: 10.1021/acs.jpca.3c04434
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Stern Layer Water Molecules, Total Potentials, and Energy Densities at Fused Silica:Water Interfaces for Adsorbed Alkali Chlorides, CTAB, PFOA, and PFAS

HanByul Chang,
Emilie H. Lozier,
Emily Ma
et al.

Abstract: We have employed amplitude- and phase-resolved second-harmonic generation spectroscopy to investigate ion-specific effects of monovalent cations at the fused silica:water interface maintained under acidic, neutral, and alkaline conditions. We find a negligible dependence of the total potential (as negative as −400 mV at pH 14), the second-order nonlinear susceptibility (as large as 1.5 × 10–21 m2 V–1 at pH 14), the number of Stern layer water molecules (1 × 1015 cm–2 at pH 5.8), and the energy associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 94 publications
(221 reference statements)
0
3
0
Order By: Relevance
“…4,8−28 In particular, the Geiger group demonstrated that measurement of the χ total (2) phase in an off-resonance SHG experiment enables the surface potential and χ SL (2) to be determined. [10][11][12][13][14]29,30 Another major contribution to the field has been the development of second harmonic scattering (SHS) experiments and the accompanying theory by the Roke group to obtain the surface potential and χ SL (2) for colloidal nanoparticles in solution. 8,31−36 The Wei group developed a scheme based on off-resonance SHG where scanning the wavelength was an effective means of varying the coherence length if the nonlinear susceptibility remains constant, thereby facilitating the separation of χ SL (2) and χ DL (2) and extracting the surface potential.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,8−28 In particular, the Geiger group demonstrated that measurement of the χ total (2) phase in an off-resonance SHG experiment enables the surface potential and χ SL (2) to be determined. [10][11][12][13][14]29,30 Another major contribution to the field has been the development of second harmonic scattering (SHS) experiments and the accompanying theory by the Roke group to obtain the surface potential and χ SL (2) for colloidal nanoparticles in solution. 8,31−36 The Wei group developed a scheme based on off-resonance SHG where scanning the wavelength was an effective means of varying the coherence length if the nonlinear susceptibility remains constant, thereby facilitating the separation of χ SL (2) and χ DL (2) and extracting the surface potential.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Eisenthal’s group first demonstrated that second harmonic generation (SHG) offers the ability to tease apart the Stern layer (SL) and diffuse layer (DL) contributions to the electrical double layer (EDL) through a decomposition of the nonlinear susceptibility into χ total (2) = χ SL (2) +χ DL (2) and, in doing so, provides access to the interfacial potential . The theory behind this analysis has been further developed and refined by several groups in recent years. , In particular, the Geiger group demonstrated that measurement of the χ total (2) phase in an off-resonance SHG experiment enables the surface potential and χ SL (2) to be determined. ,, Another major contribution to the field has been the development of second harmonic scattering (SHS) experiments and the accompanying theory by the Roke group to obtain the surface potential and χ SL (2) for colloidal nanoparticles in solution. , The Wen group developed a scheme based on off-resonance SHG where scanning the wavelength was an effective means of varying the coherence length if the nonlinear susceptibility remains constant, thereby facilitating the separation of χ SL (2) and χ DL (2) and extracting the surface potential . However, there is a selectivity advantage to probing the water response on resonance with a water-specific vibrational mode as in SFG experiments. , Hence, a two-angle SFG method has been proposed to separate the two EDL components and was recently experimentally realized .…”
Section: Introductionmentioning
confidence: 99%
“…We recently advanced nonresonant second-order nonlinear spectroscopy to probe specific ion interactions at fused silica: aqueous interfaces via the SHG phase and amplitude. This approach avoids the strong absorber problem of liquid water and provides the total interfacial potential as well as the second-order nonlinear susceptibility across interfaces in contact with ions of various chemical identities. We now employ this method to quantify the adsorbed ion density for Al 3+ , Mg 2+ , and Na + cations at fused silica surfaces maintained at pH 4, and during exposure to varying concentrations of the metal cation chlorides.…”
Section: Introductionmentioning
confidence: 99%